ACCESS: a featureless optical transmission spectrum for WASP-19b from Magellan/IMACS. Issue 2 (4th October 2018) - Espinoza, Néstor; Rackham, Benjamin V; Jordán, Andrés; Apai, Dániel; López-Morales, Mercedes; Osip, David J; Grimm, Simon L; Hoeijmakers, Jens; Wilson, Paul A; Bixel, Alex; McGruder, Chima; Rodler, Florian; et al.
ABSTRACT: The short-period (0.94-d) transiting exoplanet WASP-19b is an exceptional target for transmission spectroscopy studies, due to its relatively large atmospheric scale height (∼500 km) and equilibrium temperature (∼2100 K). Here, we report on six precise spectroscopic Magellan/IMACS observations, five of which target the full optical window from0.45 to 0.9 μ m and one targeting the0.4–0.55 μ m blue-optical range. Five of these data sets are consistent with a transmission spectrum without any significant spectral features, while one shows a significant slope as a function of wavelength, which we interpret as arising from photospheric heterogeneities in the star. Coupled with HST /WFC3 infrared observations, our optical/near-infrared measurements point to the presence of high altitude clouds in WASP-19b's atmosphere in agreement with previous studies. Using a semi-analytical retrieval approach, considering both planetary and stellar spectral features, we find a water abundance consistent with solar for WASP-19b and strong evidence for sub-solar abundances for optical absorbers such as TiO and Na; no strong optical slope is detected, which suggests that if hazes are present, they are much weaker than previously suggested. In addition, two spot-crossing events are observed in our data sets and analysed, including one of the first unambiguously detected bright -spot-crossing events on an exoplanet host star.